IMPROVING STUDENTS SPEAKING SKILLS THROUGH THE ROLE PLAYING METHOD AT X GRADE OF SMK TEKNOLOGI NASIONAL BEKASI - Luk Luk Nihmatu Rohmah; Subadar Subadar (Universitas Panca Sakti Bekasi, 2022)
This study aims to improve speaking skills through the role-playing method in class X students at SMK Teknologi Nasional Bekasi. The research subjects were 36 students from class X SMK Teknologi Nasional Bekasi. Reseachers focused on qualitative research by using triangulation, the results from three data sources, namely documentation, interviews, and observations. In this study, researchers used data in the form of written and spoken words and observed the behavior of the object of research. The data comes from structured field interviews conducted by several sources involved in this research. By playing the role of students, they will be more enthusiastic and see learning. Besides that, it also increases confidence, so it is hoped that students' speaking skills will also increase. The use of role-playing makes speaking and learning activities more fun and interesting. This is because role play helps students become confident in situations where students have difficulty in conversation. Moreover, this method is fun and most of the students agree that their learning leads to better learning. In role-playing, the world of the classroom is expanded to include the outside world. This offers a wider range of language opportunities. So, students can be anyone and in any situation they want